Noise Calculation Method for Deep Groove Ball Bearing With Considering Raceway Surface Waviness and Roller Size Error - Zhang, Qitao; Yang, Jiapeng; An, Qi (Frontiers in Mechanical Engineering, 2018)
Rolling bearing is a kind of important part of mechanical equipment, and the noise of the rolling bearing is also one of the important criteria for evaluating the quality of a rolling bearing. In the past, researches on rolling bearings are mainly on bearing vibration when people study the noise of bearings. Few studies have established rolling bearing’s noise model. In this paper, a mathematical model for calculating the inner ring’s axis center orbit and ball center’s trajectory of bearing is established based on the mechanics theory with considering raceway waviness and ball size error. Combined with the acoustics theory, a noise calculation model for deep grove ball bearing is established by taking the bearing inner ring and rolling balls as cylindrical sound source and spherical sound source respectively by using the single source compound method. The influences of waviness wave number, waviness amplitude, bearing speed, bearing load and ball size errors on bearing noise at a fixed measuring point are studied by numerical calculation. Results show that with the increase of the waviness wave number, the bearing SPL(Sound Pressure Level) will change with irregular way. With the increase of waviness amplitude, bearing speed, bearing load and ball size error band, the bearing SPL will increase.